Le sexe du militantisme - Fillieule, Olivier; Roux, Patricia (Presses de Sciences Po, 2009)
Le sexe du militantisme propose une analyse de la (re)production des rapports de pouvoir au travers des pratiques militantes, saisissant les logiques par lesquelles les inégalités de genre, de classe et de race imprègnent le militantisme, qu'il soit de gauche ou de droite, progressiste ou conservateur. Premier ouvrage en français à explorer le militantisme dans une perspective de genre à partir de recherches empiriques sur les partis, les syndicats et les mouvements sociaux, il rassemble des politistes, sociologues, anthropologues et historiennes dont le souci est de ne pas appréhender les luttes politiques comme si elles étaient « neutres » et non sexuées. Une contribution majeure à l'étude des mobilisations collectives qui complète les analyses classiques, aveugles aux rapports de genre.
Keywords: LGBTQIA2+; amérique du nord; amérique latine; amériques; anarchisme; anthropologie; approches et analyses; asie; canada; caraïbes; discipline; europe; france; genre; guyane française; histoire; hétérosexisme; identités LGBTQIA2+; inégalités; israël; italie; militance; mouvements sociaux; patriarcat; québec; racisme; rapports sociaux; rapports sociaux de sexe; ressource en ligne; régions géographiques; science politique; science politique et droit; sciences humaines; sociologie; syndicat; système colonial; systèmes d'oppressions; thématiques; violences

Sexual Attitudes and Double Standards: A Literature Review Focusing on Participant Gender and Ethnic Background - Fugère, Madeleine A.; Escoto, Carlos; Cousins, Alita J.; Riggs, Matt L.; Haerich, Paul (Sexuality & Culture : An Interdisciplinary Quarterly, 2008)
We conducted a review of literature regarding sexual attitudes and double standards, focusing on participant gender and ethnic background. We found that men had more permissive sexual attitudes than women, and that African Americans had the most permissive sexual attitudes, followed by White Americans, then by Hispanic Americans and Asian Americans. The literature regarding sexual double standards was mixed; some studies showed evidence of continued sexual double standards and some studies showed the absence of sexual double standards. In some studies, men were more likely to endorse the sexual double standard than women. We found only one article addressing sexual double standards using ethnic background as a quasi-independent variable; this research revealed that non-North American (Russian and Japanese) samples were more likely to endorse the traditional double standard, that sex is more acceptable for men than for women.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; asie; cours; discipline; europe; japon; premier cycle; psychologie; périodes historiques; rapports sociaux de sexe; ressource en ligne; russie; régions géographiques; sciences humaines; sciences sociales; sex2283; sexisme; sexologie; sexualité; systèmes d'oppressions; thématiques; états-unis

Femmes, ethnicité et religion : la communauté tamoule hindoue du Sri Lanka à Montréal - St-Germain Lefebvre, Catherine (Université du Québec à Montréal, 2008)
Convaincue que les femmes, de par leur rôle dans les rapports sociaux de sexe, ont un rôle important à jouer dans la transmission de l'identité ethnique aux jeunes générations, nous avons voulu, dans ce mémoire, mettre à jour ce phénomène tel qu'il se déploie dans la communauté tamoule du Sri Lanka immigrée à Montréal. La perspective féministe en influence la trame de fond, contribuant à orienter le choix du sujet ainsi que son traitement. Ce mémoire est le fruit d'une recherche exploratoire de type qualitatif. Il repose sur un terrain de recherche mené au temple hindou Thiru Murugan situé à Dollard-des-Ormeaux, municipalité de l'ouest de l'île de Montréal. Il a pour objectif de définir la contribution spécifique de femmes de cette communauté à la « production de l'ethnicité » tamoule, au sens entendu par la sociologue des relations ethniques, Danielle Juteau. Ce mémoire s'appuie sur un cadre théorique contribuant à jeter les bases d'une définition sociologique de l'ethnicité, où non seulement le rôle des femmes dans sa production/reproduction est mise de l'avant, mais où se dégage également l'importance de la composante religieuse dans l'affirmation ethnique, particulièrement en contexte migratoire. Cette recherche analyse d'une part la perception du rôle des femmes dans les rapports de sexe tels qu'ils se déploient dans la communauté tamoule montréalaise et telle qu'elle a été exprimée par les personnes interrogées dans le cadre de cette étude. Il s'attarde d'autre part à l'implication des femmes de cette communauté dans la transmission de la langue, de la religion et de la culture. Ce mémoire démontre que les idéaux associés à la conception de la féminité influencent à· maints égards le rôle des femmes dans les rapports sociaux de sexe à l'oeuvre dans la communauté étudiée. Ce rôle amène celles-ci à s'impliquer activement dans la transmission de leur identité ethnique auprès des générations nées au Québec. De plus, la pratique religieuse jouant un rôle important dans la formation identitaire de nos répondant(e)s, la dimension religieuse est omniprésente dans le bagage ethnique transmis par les femmes aux jeunes générations. Par leur travail actif et conscient lié à la transmission de la langue, de la culture et de la religion aux jeunes de la communauté, ces femmes participent activement à reproduire les frontières ethniques de leur communauté et contribuent, par cela, à la « production de l'ethnicité » tamoule hindoue du Sri Lanka en contexte québécois. ______________________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : Femmes, Ethnicité, Religion, Transmission, Hindouisme, Tamoul, Sri Lanka.
Keywords: IREF; amériques; approches et analyses; asie; discipline; femmes* tamoules; hindouisme; montréal; mémoires/thèses; rapports sociaux de sexe; ressource en ligne; régions géographiques; science des religions; sciences humaines; sri lanka

South Asian transnational marriages in comparative perspective - CHARSLEY, KATHARINE; SHAW, ALISON (Global Networks, 2006)
Abstract This issue on South Asian transnational marriages brings diverse practices and networks into detailed ethnographic focus. Gender and agency are key themes explored in the collection, as well as the potential and actual transformation of gendered status resulting from marrying a migrant or joining a spouse overseas. The introduction identifies some common threads. Several articles challenge the assumption of wives' passivity in arranged marriages or in their joining husbands overseas, while one highlights the less-documented experiences of men who migrate to join wives working abroad. The collection also offers insights into the cultural and emotional reasons for such marriages, complementing analyses that stress strategic motivations, and noting the emotional consequences of separation and new household formations for the experiences of marriage and parenthood. Marriage emerges as an important means of producing and transforming transnational networks, while marriage practices and dynamics are themselves transformed in the process.
Keywords: 2000 à aujourd'hui; 2000-2009; anthropologie; approches et analyses; asie; asie du sud; cours; discipline; ethnographie; histoire et politique; mariage; migration; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sex2283; thématiques

Aspiration, reunification and gender transformation in Jat Sikh marriages from India to Canada - MOONEY, NICOLA (Global Networks, 2006)
In this article I explore marriage as a strategy of family migration among a transnational community of middle-class Jat Sikhs. Family reunification and status aspirations are examined as central concerns of the transnational movement of Jat Sikhs from India to Canada. It is argued that Jat Sikh transnationalism and gender are mutually-constitutive: migration strategies can construct women, as well as men, as agents of marital citizenship, and in facilitating migration, transnational marriage may transform practices and notions of gender and status. The article is based on preliminary ethnographic research among Jat Sikh brides in Toronto and Vancouver, and forms part of a larger study of gender, modernity and identity in Indo-Canadian Jat Sikh marriages.
Keywords: amériques; anthropologie; approches et analyses; asie; canada; colombie-britannique; cours; discipline; famille; histoire et politique; inde; intersectionnalité; justice sociale; mariage; mariages transnationaux; migration; ontario; premier cycle; ressource en ligne; régions géographiques; sciences humaines; sex2283; thématiques; toronto; vancouver

The nature of gender: work, gender, and environment - Nightingale, Andrea (Environment and Planning D: Society and Space, 2006)
Le genre est depuis longtemps reconnu comme important dans les questions environnementales, mais la manière de conceptualiser le lien entre genre et environnement fait l’objet de nombreux débats. Les théories féministes sur les femmes et le genre ont évolué, tout comme les conceptualisations sur le genre et l’environnement, ce qui a donné lieu à un débat clé au sein de l’écoféminisme et des littératures associées sur la question de savoir s’il existe une relation essentielle ou contingente entre les femmes et les environnements naturels. En géographie, la plupart des écologistes politiques partent du principe que le lien entre genre et environnement est une relation contingente, et étudient donc la manière dont les relations de genre sont saillantes dans la construction symbolique et matérielle des questions environnementales. Dans cet article, je cherche à m’appuyer sur ce travail et à soulever à nouveau la question de la manière dont le genre est conceptualisé par rapport à l’environnement. Je commence par passer brièvement en revue certains des travaux qui ont été réalisés sur le genre et l’environnement, puis je m’inspire du féminisme post-structural pour suggérer que le genre lui-même a été sous-théorisé dans les travaux sur l’environnement. Une fois que le genre est reconceptualisé en tant que processus, la relation dynamique entre le genre, l’environnement et d’autres aspects de la vie sociale et culturelle peut être mise en évidence. Il en ressort que les écologistes politiques doivent examiner la question du genre au-delà du foyer et de la communauté, et reconceptualiser le lien entre le genre et l’environnement. Une étude de cas sur la foresterie communautaire au Népal est utilisée pour illustrer l’importance d’interroger les processus par lesquels les relations entre les sexes deviennent saillantes et sont reproduites symboliquement et matériellement.
Keywords: approches et analyses; asie; discipline; environnement; géographie; histoire et politique; népal; politique écologique; post-structuralisme; projet charge mentale; régions géographiques; sciences humaines; sociologie; thématiques; écoféminisme

‘Who is the Developed Woman?’: Women as a Category of Development Discourse, Kumaon, India - Klenk, Rebecca M. (Development and Change, 2004)
This article analyses gendered discourses of development in rural North India, and addresses the usefulness of recent scholarship on development as ‘discourse’ for understanding connections between development and subjectivity. This scholarship is an excellent point of departure for exploring the contradictions inherent in the institutionalization of economic development and the global reach of its discourses, but it has focused primarily upon development as discourse at official sites of deployment, while paying less attention to how specific discourses and processes of development are appropriated by those constituted as beneficiaries of development. The under-theorization of this aspect has meant that the range of processes through which development projects may encourage new subject positions are poorly understood. By investigating what some women in rural Kumaon have made of their own development, this article contributes to emerging scholarship on development and subjectivity with an ethnographic analysis of the polysemic enthusiasm for development expressed by some of its ‘beneficiaries’.
Keywords: Kumaon; anthropologie; approches et analyses; asie; cours; discipline; développement; féminisme décolonial; histoire et politique; inde; pol4022; premier cycle; relations internationales; ressource en ligne; régions géographiques; science politique; science politique et droit; sciences humaines; thématiques

Transnational migration theory in population geography: gendered practices in networks linking Canada and India - Walton-Roberts, Margaret (Population, Space and Place, 2004)
Geographers have recently suggested that transnational migration theory can contribute to the development of a critical population geography. What might such a critical population geography look like? In this paper I explore this in three ways. Firstly I offer some comments on why geographers have been slow to adopt a transnational focus on migration, and secondly I examine how gender has been underplayed in transnational literature. Thirdly I draw upon some examples from research on transnational immigrant networks between Canada and India. I focus on the specifics of Punjabi marriage migration networks to demonstrate how the practice of spousal selection has become globalised for certain diasporic communities. These examples offer a preliminary illustration of what a critical population geography, attuned to issues of gendered transnational processes, might contribute to current debates. Copyright © 2004 John Wiley & Sons, Ltd.
Keywords: amériques; approches et analyses; asie; canada; cours; discipline; géographie; histoire et politique; inde; mariage; mariages transnationaux; migration; premier cycle; punjab; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sex2283; thématiques

Rocking Sexualities: Iranian Migrants' Views on Sexuality - Ahmadi, Nader (Archives of Sexual Behavior : The Official Publication of the International Academy of Sex Research, 2003)
The purpose of this article is to put forward a theoretical discussion about Islamic views of sexuality and by means of an example show how Iranian immigrants in Sweden view sexuality and sexual culture. Building on theories that compare individualistic and holistic ways of thinking, the article seeks to elucidate the impact of basic cultural qualities on the formation of sexualities. The conclusion of the article is that the encounter with the Swedish way of thinking and the Swedish sexual culture seems to have influenced Iranian migrants' views on the nature of the relationship between couples and sexual decision making within the relationship. Exposed to an individualistic ideology and lifestyle in Sweden, Iranian migrants show a clear tendency to revise their previous holistic way of thinking, especially in regard to sexuality: the traditional, authoritarian, patriarchal sexual relationship among Iranian migrants in Sweden is giving way to more egalitarian relationships, and a relatively strong tendency towards a similarity of views between the sexes regarding sexuality can be observed. The most important change that could be observed in regard to the respondents in the study is probably an increased individualism.
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; asie; cours; discipline; europe; inégalités; iran; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sciences sociales; sex2283; sexisme; sexualité; suède; systèmes d'oppressions; thématiques; travail social

« Sex and the City » : la prostitution à l’ère des migrations mondiales - Robinson, Lillian S. (Recherches féministes, 2002)
Comme caractéristique du développement capitaliste, la migration économique a toujours entraîné le travail sexuel. À l’heure de la mondialisation, cela signifie pour beaucoup de femmes, qui émigrent du village à la grande ville dans leur propre pays ou du pays natal à l’étranger, un choix imposé par les circonstances. Cet article examine surtout la décision d’émigrer, les moyens empruntés et la situation à l’étranger de celles - la grande majorité, d’ailleurs – qui n’ont pas été victimes d’un trafic, mais qui ont exercé ce choix imposé. Le rôle dans l’émigration des travailleuses sexuelles et des clients « émigrés » en tant que touristes sexuels fait partie de la discussion, ainsi que d’autres caractéristiques économiques et culturelles.Summary As a feature of capitalist development, economic migration has historically entailed sex work as one of its components. In the age of globalization, this means a forced choice for many women, as they move from the village to the city in their own countries and across international borders. The present article focuses on the decision making process, the means of migration, and the experience in the urban site, national or international, of those – the vast majority – who have not been "trafficked", but have made this forced choice their life strategy. The impact on sex worker migration of customer "migration" in the form of sex tourism is discussed, along with the other economic and cultural factors.
Keywords: 1900-1999; afrique; amériques; approches et analyses; asie; capitalisme; cours; discipline; droits des femmes*; europe; féminisme du sud; féminisme décolonial; globalisation; his4860; histoire et politique; immigrantes clandestines; immigration; inde; industrie du sexe; inégalités; migration; pauvreté; premier cycle; périodes historiques; racisme; rapports sociaux de sexe; régions géographiques; sciences humaines; sciences sociales; sexisme; sociologie; système colonial; systèmes d'oppressions; thématiques; tourisme sexuel; travail; travail des femmes*; travail du sexe

Doing fieldwork on women in theocratic Islamic states: A critique of the politics of empiricism - Mojab, Shahrzad (Resources for Feminist Research, 2001)
This paper examines the way some feminist advocates of cultural relativism adopt positivism and empiricism in order to discredit the radical critique of Islamization of gender relations in Iran. It argues that relativists use the positivist/empiricist cult of experience and objectivity in order to undermine the critique of policies and practices that oppress the women of Iran. The choice of a method of inquiry is not based on methodological considerations only. The researcher's political preferences, implicit or explicit, plays a significant role in the entire research process, especially in the study of sensitive issues. Although one may identify a methodological tradition with a certain brand of politics, the paper argues that methodological paradigms enter into changing relationships with structures of power.
Keywords: approches et analyses; asie; cours; discipline; discours dominant; fem1000; iran; méthodologie; premier cycle; ressource en ligne; régions géographiques; sciences humaines; systèmes d'oppressions; épistémologie